Improved InGaN/GaN light-emitting diodes with a p-GaN/n-GaN/p-GaN/n-GaN/p-GaN current-spreading layer : errata - Zhang, Zi-Hui (2013)
The errata consists of the correction to one typo of the reach-through breakdown voltage for each p-GaN/n-GaN/p-GaN junction [Opt. Express 21, 4958-4969 (2013)].